Exercise-induced ‘browning’ of adipose tissues - Aldiss, Peter; Betts, James A.; Sale, Criag; Symonds, Michael E. (Elsevier, 2018)
Global rates of obesity continue to rise and are necessarily the consequence of a long-term imbalance between energy intake and energy expenditure. This is the result of an expansion of adipose tissue due to both the hypertrophy of existing adipocytes and hyperplasia of adipocyte precursors. Exercise elicits numerous physiological benefits on adipose tissue, which are likely to contribute to the associated cardiometabolic benefits. More recently it has been demonstrated that exercise, through a range of mechanisms, induces a phenotypic switch in adipose tissue from energy storing white adipocytes to thermogenic beige adipocytes. This has generated the hypothesis that the process of adipocyte ‘browning’ may partially underlie the improved cardiometabolic health in physically active populations. Interestingly, ‘browning’ also occurs in response to various stressors and could represent an adaptive response. In the context of exercise, it is not clear whether the appearance of beige adipocytes is metabolically beneficial or whether they occur as a transient adaptive process to exercise-induced stresses. The present review discusses the various mechanisms (e.g. fatty acid oxidation during exercise, decreased thermal insulation, stressors and angiogenesis) by which the exercise-induced ‘browning’ process may occur.